Single cell behavior in T cell differentiation - Rohr, Jan C.; Gerlach, Carmen; Kok, Lianne; Schumacher, Ton N. (Trends in immunology, 2014)
•Upon antigen encounter, proliferating T cells diversify in function and phenotype.•Lineage tracing demonstrates that the output of individual T cells is highly variable.•Reproducibility of T cell responses is due to the averaging of disparate single cell behaviors.•Variability in T cell output may be driven by cell-intrinsic or cell-extrinsic mechanisms. Upon primary infection, naïve T cells that recognize their cognate antigen become activated, proliferate, and simultaneously differentiate into various subsets. A long-standing question in the field has been how this cellular diversification is achieved. Conceptually, diverse cellular output may either arise from every single cell or only from populations of naïve cells. Furthermore, such diversity may either be driven by cell-intrinsic heterogeneity or by external, niche-derived signals. In this review, we discuss how recently developed technologies have allowed the analysis of the mechanisms underlying T cell diversification at the single cell level. In addition, we outline the implications of this work on our understanding of the formation of immunological memory, and describe a number of unresolved key questions in this field.